The Threat Review and Prioritization trap: how the FBI's new Threat Review and Prioritization process compounds the Bureau's oldest problems. Issue 5 (28th July 2016) - Tromblay, Darren E.
Abstract: In the nearly 15 years since the events of 11 September 2001, the Federal Bureau of Investigation (FBI) has undertaken a succession of efforts to become an agency capable of fulfilling the intelligence functions with which it has been entrusted. However, historically, the FBI's experience with intelligence has been reactive due to a law enforcement culture that closed cases rather than identified ways to keep opportunities for collection open, as well as bureaucratic wariness due to the differing expectations from one Presidential administration to the next. The Threat Review and Prioritization (TRP) process is the most recent iteration of the Bureau's attempt to organize as an intelligence service. However, TRP is informed not by a mission of developing intelligence that will help to disrupt emerging threats or exploit opportunities at both the strategic (policymaking) and tactical (arrests), but instead reactively focuses on the threats which have become fully manifest within the FBI's own domain. TRP leaves the US at a disadvantage vis-à-vis state and non-state adversaries and competitors. Organizationally, it institutionalizes the shortcomings of reactivity and insularity that were the unfortunate characteristics of the pre-9/11 FBI.